Development of the Value Inquiry Learning Model to Improve Conceptual Understanding and Social Attitudes in Thematic Learning - Ani Siti Anisah; Sapriya Sapriya; Kama Abdul Hakam; Ernawulan Syaodih; Nordin bin Mamat (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractSchool learning is seen as emphasizing the achievement of cognitive aspects, while affective aspects tend to be neglected. Thus causing imbalances in the formation of students' overall competence. To answer these challenges, a Value Inquiry learning model was developed that can balance cognitive and affective aspects integrated in thematic learning. This research used a modified Research & Development approach through three stages of implementation: preliminary study, model development, and model validation test. This research involved five elementary schools in Garut Regency. The instruments used included expert validation questionnaires, observation sheets, attitude questionnaires, and learning outcome tests. The limited and broad trials showed a significant increase in both concept understanding and students' social attitudes, it was shown by the results of the N-Gain analysis with an increase of 29.48% in the limited experimental class test with a low interpretation, 69.06% in the broad test phase I, 69.98% in phase II, and 70.10% in the validation test with a moderate interpretation. The effectiveness test results with a value of 0.701 which indicates that the Value Inquiry learning model is quite effective in improving students' concept understanding and social attitudes. Thus, this model is very relevant and practical to be applied.Keywords: learning models, value inquiry, social attitudes, characteristics of elementary school students.AbstrakPembelajaan di sekolah dipandang lebih menekankan pada pencapaian aspek kognitif, sementara aspek afektif cenderung terabaikan. Sehingga menyebabkan ketimpangan dalam pembentukan kompetensi utuh siswa. Untuk menjawab tantangan tersebut dikembangkan model pembelajaran Value Inquiry yang dapat menyeimbangkan aspek kognitif dan aektif yang terintegrasi dalam pembelajaran tematik. Penelitian ini menggunakan pendekatan Research & Development yang dimodifikasi melalui tiga tahap pelaksanaan: studi pendahuluan, pengembangan model, dan uji validasi model. Penelitian ini melibatkan lima sekolah dasar di Kabupaten Garut. Instrumen yang digunakan melipui angket validasi ahli, lembar observasi, angket sikap, dan tes hasil belajar. Pada uji coba terbatas dan luas menunjukkan peningkatan yang signifikan baik dalam pemahaman konsep maupun sikap sosial siswa, hal itu ditunjukkan oleh hasil analisis N-Gain dengan peningkatan sebesar 29,48% pada uji kelas eksperimen terbatas dengan interpretasi rendah, 69,06% pada uji luas tahap I, 69,98% pada tahap II, dan 70,10% pada uji validasi dengan interpretasi sedang. Hasil uji efektivitas dengan nilai 0,701 yang menunjukkan bahwa model pembelajaran Value Inquiry  cukup efektif dalam meningkatkan pemahaman konsep dan sikap sosial pesrta didik. Dengan demikian, model ini sangat relevan dan praktis untuk diterapkan.Kata kunci: model pembelajaran, value inquiry, sikap sosial, karakteristik siswa sekolah dasar.